Daily volatility behaviour in agricultural futures market - Ang, Kelly (2009)
This Applied Research Project investigates the effect of daily trading volume and open interest on the daily volatility of agricultural commodities futures. Past studies have shown that trading volume exhibits a positive relationship with return volatility while open interest is negatively correlated to return volatility. Although these two relationships are widely documented in much of the existing literature, most of the focus has been on financial futures, with limited studies on commodities futures. This paper seeks to address this gap by examining agricultural futures, and to compare and discuss the effects of these two variables on volatility under four different market conditions: high volume/high open interest, high volume/low open interest, low volume/high open interest, and low volume/high open interest. We look into the Corn, Soybean, and Wheat agricultural commodities between the years of 1995 and 2008. Using the Pearson correlation and multivariate models, we establish that the two relationships are consistent with previous findings.